2011
DOI: 10.1007/s12350-011-9454-0
|View full text |Cite
|
Sign up to set email alerts
|

85% of maximal age-predicted heart rate is not a valid endpoint for exercise treadmill testing

Abstract: Achievement of 85% MPHR is not a valid diagnostic or functional exercise endpoint because it significantly underestimates exercise capacity and inducible ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 20 publications
2
16
0
1
Order By: Relevance
“…One of these patients was on beta-blocking medication and the other showed ischaemia on MPI. Both patients achieved a high exercise workload (seven or more metabolic equivalents), which has been shown to have more value than attaining an arbitrarily chosen target heart rate [19]. PET MPI provided fewer equivocal results than SPECT, suggesting that it improves reader confidence as an important component of the report.…”
Section: Discussionmentioning
confidence: 95%
“…One of these patients was on beta-blocking medication and the other showed ischaemia on MPI. Both patients achieved a high exercise workload (seven or more metabolic equivalents), which has been shown to have more value than attaining an arbitrarily chosen target heart rate [19]. PET MPI provided fewer equivocal results than SPECT, suggesting that it improves reader confidence as an important component of the report.…”
Section: Discussionmentioning
confidence: 95%
“…Jain et al 10 have recently shown how terminating exercise at 85% of MPHR can significantly underestimate the amount of ischemia. However, certain conditions such as orthopedic, peripheral vascular, psychologic, or treadmill unfamiliarity can prevent achieving adequate heart rate responses despite an elevated perceived level of exertion.…”
Section: Discussionmentioning
confidence: 99%
“…A maximal symptom-limited exercise bicycle stress test with continuous 12-lead ECG and blood pressure monitoring was performed [6]. The test commenced with a workload of 25 or 50 W depending on the patient's estimated performance level; every 2 min, the load was increased by 25 W. The test was terminated at maximum exhaustion or prematurely in the case of malignant arrhythmias, severe ST-segment deviations or at a decreasing systolic blood pressure >20%.…”
Section: Methodsmentioning
confidence: 99%